A scandal made at midnight - Hewitt, Kate (Harlequin presents, 2022)
"The venerable Rossi brand, now threatened with being labeled stuffy, needs an image overhaul, and new CEO Alessandro Rossi has found the perfect media influencer to court. Only it's her plain older stepsister who catches his attention! Liane Blanchard is used to living life in the shadows, but Alessandro's heated gaze across a Parisian ballroom sets her body alight! She agrees to a sizzling fling, knowing it's all emotionally guarded Alessandro can offer. They're risking a scandal, but it's worth it for a taste of the fairy tale..." -- Page [4] cover.